Legal system of agricultural companies with legal entity - Eugenia Gabriela Leuciuc (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
From the point of view of the corporative organization with legal entity, in agriculture, the activity can be conducted either under the form of companies regulated by Law no. 31/1990, republished, or the form of agricultural companies regulated by the Second Title of Law no. 36/1991 regarding agricultural companies and other forms of association in agriculture, altered by the Emergency Ordinance no. 125/2006 starting with 26.05.2007, or the form of agricultural cooperative regulated by Law no. 566/2004 on the agricultural cooperative, the way it was altered. Such forms of company acknowledge a series of particularities, as they are destined in principle to agricultural exploitations of large dimensions, where are concentrated both real estates and capitals. The legal entity confers them an apparent independency of the patrimony, which is distinct from that of the members, but which, as against the recent regulation of the companies without legal entity and as against the notional delimitation of the patrimony of affectation, corroborated with the procedural institutionalization characterizing their constitution, no longer represent the acknowledged relevance. The analysis of these forms of the development of the activity in agriculture is yet of actuality, not only because they will continue existing in the Romanian economy, but also because they allow the infusion of capital and that of foreign models of organization of agricultural activities in forms already known.
Keywords: 330; agricultural exploitations; legal entity; agricultural company